2020
DOI: 10.1590/s1980-6574202000020169
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison in the Wingate test between standing and seated positions in competitive cyclists

Abstract: The current study aimed to compare the anaerobic power output through the Wingate test in different positions, i.e., standing and seated, and identify the relationship between power-output and body mass. Methods:Eleven male competitive cyclists (age: 30.3 ± 4.7 years; body mass: 73.7 ± 7.7 kg; body fat: 11.3 ± 4.2%) were submitted to two sessions of the Wingate test (WT) in different positions, on different days. Results: The peak power (W), average power (W), relative peak power (W•kg -1 ), relative average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Standing while sprinting has a positive effect on power output when compared with a seated position (Bertucci et al, 2005;Bertucci et al, 2008;Merkes et al, 2020;Millet et al, 2002;Reiser et al, 2002;Rohsler et al, 2020). For example, Reiser and colleagues (Reiser et al, 2002) observed a 6 to 8% improvement in peak and mean power output while standing (19.4 and 11.0 W•kg-1, respectively) during a 30 s Wingate, compared with sitting (17.9 and 10.4 W•kg-1, respectively).…”
Section: Cyclist's Body Position During Road Cycling Sprintingmentioning
confidence: 99%
“…Standing while sprinting has a positive effect on power output when compared with a seated position (Bertucci et al, 2005;Bertucci et al, 2008;Merkes et al, 2020;Millet et al, 2002;Reiser et al, 2002;Rohsler et al, 2020). For example, Reiser and colleagues (Reiser et al, 2002) observed a 6 to 8% improvement in peak and mean power output while standing (19.4 and 11.0 W•kg-1, respectively) during a 30 s Wingate, compared with sitting (17.9 and 10.4 W•kg-1, respectively).…”
Section: Cyclist's Body Position During Road Cycling Sprintingmentioning
confidence: 99%